Psychological safety mediates attendance and recovery-related outcomes within the Phoenix: a sober-active community - Heinrich, Katie M.; Wyker, Brett; Collinson, Beth; Eddie, David; Best, David; Hillios, Jacquelyn (Frontiers in Public Health, 2025)
BackgroundPeople in recovery from a substance use disorder often have difficulties forming pro-social relationships or accessing supportive communities. Providing psychological safety within recovery communities may be uniquely beneficial, yet psychological safety has mostly been studied among professional organizations and not among vulnerable populations. This program evaluation study examined associations between attendance, psychological safety, and retrospective recovery-related changes.MethodsParticipants included 204 members of The Phoenix (13% response rate) who completed a survey that addressed recovery status and current perceptions of psychological safety, with hope, connection, empowerment, motivation to stay sober, mental health and physical health at 3-months and thinking back to baseline (i.e., “thentest”). Demographic information and attendance data were also collected.ResultsStructural equation modeling found a good fit for the model (χ2 = 187.40, p = 0.23; RMSEA =0.049, GFI = 0.90, CFI = 0.98, SRMSR = 0.05.) and all path coefficients were statistically significant (p < 0.05). Participants’ perceived psychological safety fully mediated the relationship between attendance and recovery-related outcomes. Attendance was also directly and positively associated with physical health.ConclusionDue to positive improvements in health and recovery-related outcomes mediated by psychological safety, results show benefits of attending events hosted by The Phoenix for those in recovery from substance use. Additional research should further validate the importance of psychological safety as a key mediator of the recovery process.